PENTINGNYA KETERAMPILAN BERBAHASA INDONESIA PADA KEGIATAN PEMEBELAJARAN SEKOLAH DASAR - Yemima Heginta Br Tarigan; Nana Hendra Cipta; Siti Rokmanah (STKIP Subang, 2023)
Human life is not without language activities, language is used as a means of interpersonal communication, and even language is considered a perfect language for interacting with others. To improve the ability to communicate and speak the language, it is necessary to learn the language from the beginning, since I was sitting at the basics. Then the supporting aspect of improving communication ability and good language is to master a lot of vocabulary, to master. To speak well four skills must be mastered, namely the skills of sympathy, fluency of speech, reading skills, and writing skills. The method that will be used to build this journal is library study.